Nutrient loss by runoff from rice-wheat rotation during the wheat season is dictated by rainfall duration. (15th September 2021) - Yan, Lei; Xue, Lihong; Petropoulos, Evangelos; Qian, Cong; Hou, Pengfu; Xu, Defu; Yang, Linzhang
Abstract: Clarifying the properties/features of nutrient loss from farmland surface runoff is essential for the mitigation of nutrient losses. Plough pan formation underneath topsoil is a common feature of long-term paddy soils that significantly affects water movement and nutrient runoff loss, especially during the upland season of paddy-upland rotation. To characterize the nutrients that are lost from wheat fields of paddy-wheat rotation with runoff, a field experiment was conducted in a wheat field using a simulated rainfall system from November 2019 to May 2020 in Nanjing, China. The aim of this study was to investigate the temporal characteristics of nitrogen (N) and phosphorus (P) loss under different rainfall intensities (low, 30 mm h −1 ; middle, 60 mm h −1 ; high, 90 mm h −1 ). The results showed that the time interval from the beginning of rain to the occurrence of runoff (time to runoff, Tr) was negatively correlated with "rainfall intensity" (Ri) ( P ＜0.01) but unaffected by soil moisture. Different rainfall intensities had no effect on the runoff coefficient (the ratio of the runoff volume over the precipitation, 0.14–0.17). The N and P loss concentrations in the nutrient discharge followed a power-function relationship that decreased over time ( P ＜0.01), and the peak nutrient concentration appeared during the initial runoff period (0–5 min). The N and P loss rates were the highest during the middle-to-late discharge period (15–30 min) for all intensities. In terms of cumulative nutrient losses, the amounts of TN lost were similar for all rainfall intensities, while TP significantly increased with intensity. The results revealed that nitrate-nitrogen (NOX − -N) and particulate phosphorus (PP) were the predominant forms of N and P losses. Overall, during the initial runoff period, nutrient concentration peaks, whereas the nutrient loss rate is the highest during the middle-late phase of the phenomenon. Graphical abstract: Image 1 Highlights: Simulated rainfall was used in a wheat field within a paddy-wheat rotation. The runoff coefficient was unaffected by the rainfall intensity and soil moisture. The N and P concentration was the highest during the initial runoff period. The N and P loss rates were the highest during the middle-late period. Only the TP, and not the TN, loss increased with rainfall intensity.